Mortality salience effects and status consumption–A reasoned action approach - Jolien Arendsen; Guido M. van Koningsbruggen; Marieke L. Fransen (PLoS ONE, 2026)
Prior research suggests that mortality salience (MS) can promote status consumption, yet it remains unclear how these effects are formed. To address this gap, we applied the Reasoned Action Approach, which provides a systematic framework to examine how MS may influence intentions to engage in status consumption. Study 1, a belief elicitation study, identified the set of salient beliefs related to status consumption. Study 2 revealed that MS influenced two out of 29 beliefs underlying status consumption identified in Study 1. Additionally, experiential attitude was a weaker predictor of the intention to engage in status consumption after MS. However, no effects of MS were observed on the intention to purchase status products or its determinants. Taken together, these findings suggest that, although MS may influence some underlying beliefs about status consumption, these changes are too weak to translate into meaningful differences in consumers’ behavioral intentions. By using the Reasoned Action Approach, the present research advances our understanding of how MS may or may not influence consumer intentions. It also suggests that MS’s influence on status consumption may be more limited than previously assumed.